Steric and chain length effects in the (√(3) × √(3))R30° structures of alkanethiol self-assembled monolayers on Au(111) (2011)
The translational and orientational potential energy surfaces (PESs) of n-alkanethiols with up to four carbon atoms are studied for (√(3) × √(3))R30° self-assembled monolayers (SAMs). The PESs indicate that methanethiol may form SAM structures that are not accessible for long-chain thiols. The tilt of the thiol molecules is determined by a compromise between the preferred binding geometry at the sulfur atom and the steric requirements of the alkane chains. The Au-S bond lengths, offset from the bridge position (brg), and the Au-S-C bond angles result in tilt angles of the S-C bond in the range of 55-60°. As DFT/generalized gradient approximation systematically underestimates chain-chain interactions, the binding energies are corrected by comparison to MP2 interaction energies of alkane dimers in SAM-like configurations. The resulting thiol binding energies increase by approximately 1 kcal mol-1 per CH2 group, which results in a substantial stabilization of long-chain SAMs due to chain-chain interactions. Furthermore, as the chain length increases, the accessible range of backbone tilt angles is constrained due to steric effects. The combination of these two effects may explain why SAM structures with long-chain thiols exhibit higher order in experiments. For each thiol two favorable SAM structures are found with the sulfur head group at the fcc-brg and hcp-brg positions, respectively. These domains may coexist in thermal equilibrium. In combination with the symmetry of the gold (111) surface, this raises the possibility of up to six different domains on single-crystal terraces. Reconstructions by an adatom or vacancy of ethanethiol SAMs with (√(3) × √(3))R30° lattice are also studied using PES scans. The results indicate that adsorption of thiols next to a vacancy is favorable and may lead to point defects inside SAMs. Showing potential: The translational and orientational potential energy surfaces of n-alkanethiols with up to four carbon atoms are studied for (√(3) × √(3))R30° self-assembled monolayers (SAMs, see picture). The binding energies with the van der Waals interactions corrected using MP2 calculations increase by about 1 kcal mol-1 per CH2 group. This trend and the increasingly confined accessible range of the tilt angles may contribute to the higher order observed in long-chain thiol SAMs on gold. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.